Ushul al-Fiqh Mutakallimin: Review Atas Kitab al-Ihkam fi Ushul al-Ahkam - Isnatin Ulfah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2008)
This study aims to examine the Ushul al-Fiqh approach of the Mutakallimin school through a critical study of Ibn Hazm's book al-Ihkam fi Ushul al-Ahkam. This book represents the distinctive character of the Mutakallimin method which is rational and systematic in formulating the principles of ushul fiqh. This study uses a qualitative method with a literature study approach, tracing the structure of arguments, legal sources, and Ibn Hazm's position on the method of ijtihad. The results show that al-Ihkam emphasizes the rejection of qiyas and ra'y, and offers a literal approach in understanding the text, which reflects the spirit of purifying Islamic law from elements of subjectivity. This book is one of the important works in the classical Ushul al-Fiqh discourse, especially in understanding the dialectic between rational and textual approaches in Islamic law.